Sustainability assessment in construction organisations’ project delivery practice in Nigeria - Ujene, A.O.; Oladokun, M.G. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Based on the growing ethos that construction organisations can benefit from implementing sustainable practices, this study evaluated main contractors’ project delivery practices for sustainability. The objectives were to validate set of empirically weighted criteria for construction organisations’ sustainability practice assessment. The weighted criteria were validated by assessing three main contractors’ organisations’ sustainability performance in four projects. The sustainability performance was evaluated based on sound environmental management principles, robust stakeholder engagement and responsible project management. Data were collected using questionnaire survey and project auditing. The study targeted 76 stakeholders in contractors and engineering consultancy organisations in Akwa Ibom State, Nigeria. Criterion suitability was based on respondents’ agreement score in inter-rater agreement (IRA) scale. Correlational effects were explored in published and assessed weightings using Multiple Analysis of Variance (MANOVA). The finding indicated contractors’ inclination towards sustainable construction practice must be strengthened. MANOVA correlation showed published and assessed weightings differ significantly with (Lambda (4, 2) = 0.056, p = 0.418). The study submits weighted criteria are suitable for assessing a practice. The criteria are by this means validated and form assessment benchmarks for use in the absence of standard tool. The region must institute incentive and reward systems to stimulate widespread sustainable practices application within the contracting sector.